The relationship between bariatric surgery and mental disorders: An analysis (Research, Society and Development, 2024)
Objective: To describe the relationship between bariatric surgery and mental disorders, such as anxiety and depression. Materials and Methods: This is a qualitative and narrative literature review conducted on academic databases including SciELO, PubMed, and Google Scholar, aiming to find recent studies and documents on the relationship between bariatric surgery and mental disorders. Results and Discussion: Bariatric surgery is effective, but it carries risks and complications, potentially causing rapid and drastic changes in the body and life of patients, who often struggle with mental disorders both before and after the procedure. The complex interaction between obesity, mental disorders, and bariatric surgery underscores the importance of a multidisciplinary approach in treating these patients. Conclusion: Understanding this complex relationship is essential to optimize clinical outcomes and postoperative quality of life. A comprehensive approach, considering physical, emotional, and psychological aspects, is fundamental to treatment. Ongoing research and innovative interventions are necessary to improve the care and outcomes of patients undergoing bariatric surgery.